Pemanfaatan Limbah Organik Melalui Desain Produk Sebagai Media Merangkai Bunga (Studi Kasus: Limbah Bunga) - Fitria, Anisah; Ihsan, Muhammad (Jurnal Desain Indonesia., 2024)
This research focused on findings potential usage of flower waste as a material for the product design. This is a response to the fact that the total waste production in Indonesia has gone up and most of it is organic waste which flowers are part. Events like weddings, graduations, and birthdays are occasions where a lot of flowers are ordered, but are later discarded when the occasion is over. In the data collected, it is estimated that weddings create 151 bouquets of flowers and leaves, fresh flowers that amount to 6kg which become waste. The aim of this research study is to investigate the possibility of flower waste to be utilized in aesthetic floral designs in a sustainable approach. Material Driven Design was applied in the experimental method. The experimental results show that the optimal formula for the medium of flower arranging is composition ratio of 3:1 for flowers to tapioca mixed with additive binder which is glycerol and CMC through the baking method. Therefore, the outcomes show that flower waste can be considered as a new material for floral arrangement industry, and contribute to the development of the flower waste research. Keywords: organic waste, flower waste, natural materials, product design, arranging medium